2012
DOI: 10.1093/humrep/des026
|View full text |Cite
|
Sign up to set email alerts
|

Depleted iron stores without anaemia early in pregnancy carries increased risk of lower birthweight even when supplemented daily with moderate iron

Abstract: Beginning pregnancy with non-depleted iron stores is beneficial for the maternal iron status during pregnancy and infant birthweight. These findings reaffirm the importance of health promotion to ensure that women have adequate iron stores prior to, or early in, pregnancy when supplemented with moderate daily iron doses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 30 publications
3
39
1
3
Order By: Relevance
“…In a study on the effect of Fe supplementation in pregnancy and its impact on newborns in Niger, Preziosi et al found 54 % of women to be Fe-deficient at 6 months of pregnancy (39) , which is more severe than our results. A recent study in Spain found Fe deficiency among 20 % of pregnant women in the first trimester, 54 % in the second and 66 % in the third, which is also more than in our study (40) . In a study on Swiss pregnant women (9) , Zimmermann et al found 16 % to be Fe-deficient in the second trimester and 40 % in the third, but they considered a less restrictive cut-off than us.…”
Section: Discussioncontrasting
confidence: 58%
“…In a study on the effect of Fe supplementation in pregnancy and its impact on newborns in Niger, Preziosi et al found 54 % of women to be Fe-deficient at 6 months of pregnancy (39) , which is more severe than our results. A recent study in Spain found Fe deficiency among 20 % of pregnant women in the first trimester, 54 % in the second and 66 % in the third, which is also more than in our study (40) . In a study on Swiss pregnant women (9) , Zimmermann et al found 16 % to be Fe-deficient in the second trimester and 40 % in the third, but they considered a less restrictive cut-off than us.…”
Section: Discussioncontrasting
confidence: 58%
“…Bu bebekler yenidoganlarm %6-7'sini olu §turmasina karçin, tüm yenidogan ölümlerinin ücte ikisi bu gruptandir (4,5). Demir eksikiigi anemisi olan gebe kadmlari içeren cok sayidaki çaliçmada gösterilmi §tir ki, demir verilmesi dogum agirligini iyile §tirmekte, ölüm oranini azaltmaktadir (6,7).…”
Section: Giriçunclassified
“…Demir eksikliginin fetal ve yenidogan etkilerinin önlenebilmesi için demir verilmesi mümkünse gebelik öncesinde veya erken gebelikte ba §lanmasi önerilmektedir (6).…”
Section: Giriçunclassified
“…The prevalence of ID and IDA is higher in pregnancy, and IDA affects 18-38% of pregnant women worldwide (Lopez et al 2016; World Health Organization 2015). The worldwide prevalence of ID is twice that of IDA (Camaschella 2015), and studies in Western nations report ID in as many as 60% of pregnant women (Arija et al 2013; da Costa et al 2016; Harvey et al 2016; Ribot et al 2012). …”
Section: Perinatal Iron Deficiencymentioning
confidence: 99%